Fiqh Learning at Madrasah Ibtidaiyah: Enhancing Students’ Academic Performance through a Collaborative Learning Model - Hikmat Kamal; Mahyudin Ritonga; Adam Mudinillah (STAI Hubbulwathan Duri, 2024)
In the context of Madrasah Ibtidaiyah, Fiqh is a mandatory subject facing challenges due to ineffective teaching methodologies, leading to suboptimal learning outcomes. This study explores the potential of collaborative learning models to enhance these outcomes, hypothesizing that such methods could improve student engagement and comprehension. Utilizing a quantitative approach, data were collected through a structured questionnaire administered to Fiqh teachers via Google Forms, focusing on the effectiveness of current teaching methods and their impact on student performance. The analysis indicated that collaborative learning significantly improves learning outcomes by fostering greater student cooperation in understanding Fiqh concepts. This enhancement in learning is evident in both the quality of student engagement and academic achievements. While the findings affirm the benefits of collaborative methods, the study is limited to these strategies and suggests further research into a variety of instructional techniques to broaden educational effectiveness in religious studies. The success of collaborative models in this setting supports their potential utility in similar educational contexts, recommending an expansion of research to include diverse pedagogical approaches.